(untitled) (International Journal of Management and Sustainability, 2015)
This study is an exploratory study aims to investigate the impact of employer branding personality on employee differentiation, loyalty, satisfaction and affinity among organizations in Pharmaceuticals industry in Egypt. The survey was based on corporate character scale & employee behavior indicators that had been modified and used locally. The paper surveyed literature review of the employer branding (EB) concept and employee differentiation, loyalty, satisfaction and affinity & the pharmaceutical sector overview in Egypt. The study findings employer branding impact employee differentiation, loyalty, satisfaction and affinity as illustrated through paper. Which, deeply interwoven and opens up new questions to be explored by future research identified through paper.